Reclamation Strategies for Sustainable Agriculture on Post-Mining Land: A Case Study in East Kalimantan, Indonesia - Ansahar; Sitorus, Santun; Hartrisari; Putri, Eka (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Mining activities often leave behind degraded land requiring restoration and sustainable utilization. This study aims to (1) analyze the suitability of post-mining land for agriculture, (2) assess the socioeconomic conditions of surrounding communities, and (3) evaluate sustainability factors influencing post-mining land use. A land evaluation was conducted using a matching system, while socioeconomic data were collected through purposive sampling interviews across four post-mining sites in East Kalimantan, Indonesia. The land suitability analysis identified three viable agricultural uses: rice cultivation (342.94 ha), corn production (209.51 ha), and pasture-raised cattle grazing (377.81 ha), with distribution across sites LP1, LP2, LP3, and LP4. The sustainability of each site was assessed across five dimensions: ecological, economic, social, legal, and infrastructure, using composite sustainability indices. Results showed varying sustainability levels: ecological (59.37, moderately sustainable), economic (80.35, highly sustainable), social (70.43, fairly sustainable), legal (57.42, moderately sustainable), and infrastructure (85.53, highly sustainable). These findings indicate that while economic and infrastructural conditions are favorable for sustainable land use, ecological and legal aspects require targeted improvements. The moderate social sustainability score suggests a need for greater community engagement and benefit-sharing mechanisms. These findings provide actionable insights for improving post-mining land use and promoting sustainable development in East Kalimantan, Indonesia.